Pendampingan Laporan Keuangan Digital Aplikasi Jaraya Pada UMKM Kuliner - Ahmad Syauqi; Najiatun Najiatun; Rahmat Zulknarnain; Imam Anas Mubarok (Lembaga Pengembangan Kinerja Dosen, 2024)
Assistance with digital financial reports using the Jaraya application for culinary MSMEs aims to increase the understanding and skills of MSME players in managing financial reports in a more efficient and structured way. Culinary MSMEs often face challenges in accurate and transparent financial records, which can affect their business decisions and business growth. In this program, the Jaraya application is introduced as a practical solution to simplify the process of recording transactions and creating digital financial reports. Assistance is provided through direct training, application usage simulations, and discussions to overcome problems faced by business actors. The results of this assistance show an increase in MSME players' understanding of the importance of organized financial reports and their ability to use the Jaraya application to monitor cash flow, manage profit and loss, and make better business decisions. This program is expected to have a positive impact on more efficient financial management and support the growth of culinary MSMEs in the future.